Prevalence of various reproductive disorders in buffaloes in seleniferous areas of Punjab - ATWAL, K S; PRABHAKAR, S; GHUMAN, S P S (The Indian Journal of Animal Reproduction, 2023)
Prevalence of various reproductive disorders in buffaloes in seleniferous area of Punjab revealed anestrous to be a major gynaecological problem followed by repeat breeding and abortion.